Control of propulsion and body lift during the first two stances of sprint running: a simulation study - Debaere, S.; Delecluse, C.; Aerenhouts, D.; Hagman, F.; Jonkers, I. (Journal of Sports Sciences, 2015)
The aim of this study was to relate the contribution of lower limb joint moments and individual muscle forces to the body centre of mass (COM) vertical and horizontal acceleration during the initial two steps of sprint running. Start performance of seven well-trained sprinters was recorded using an optoelectronic motion analysis system and two force plates. Participant-specific torque-driven and muscle-driven simulations were conducted in OpenSim to quantify, respectively, the contributions of the individual joints and muscles to body propulsion and lift. The ankle is the major contributor to both actions during the first two stances, with an even larger contribution in the second compared to the first stance. Biarticular gastrocnemius is the main muscle contributor to propulsion in the second stance. The contribution of the hip and knee depends highly on the position of the athlete: During the first stance, where the athlete runs in a forward bending position, the knee contributes primarily to body lift and the hip contributes to propulsion and body lift. In conclusion, a small increase in ankle power generation seems to affect the body COM acceleration, whereas increases in hip and knee power generation tend to affect acceleration less.